Reviews (Blackfriars, 1934)
Jesus Christ. His Person, His Message, His Credentials. By Léonce de Grandmaison, S.J. Jesus Raconte par le juif Errant. By Edmond Fleg After Strange Gods. By T. S. Eliot NewPsychology and Old Religion. By Edward F. Murphy, S.S.J., Ph.D. Practical Psychology. By Rudolf Allers, adapted by Vera Barclay The Breakdown of Money. An Historical Explanation. By Christopher Hollis I Commit to the Flames. By Ivor Brown THE PLAY GRAMOPHONE